ANALISIS SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN NOVEL “MATAHARI DI ATAS GILI” KARYA LINTANG SUGIANTO - Utomo, Widya Tri; Aini, Siti Noor (Penerbit Widina, Widina Media Utama, 2022)
The purpose of the research is to describe the worldview, social/cultural background, author's view of female characters, and find out the educational value contained in the novel